Education and the urban community : schools and the crisis of the cities - Hillson, Maurie; Cordasco, Francesco ;Purcell, Francis P. (New York : American Book Company, 1969)
education and the Urban Community brings together forty-nine readings dealing with the and conflicts in education that exist in urban areas. The selections attempt to move from mere description. There are included, of course, articles that deal with the description of conditions. These are needed because they serve to etch out sharply the ne from which we must move.
Section I. The City in modern America: the phenomenon of urbanization -- Section II. The School and the urban ethos: social stratification and educational denial -- Section III. The School and aspects of the community relationship -- Section IV. School organization: the technology of change and curriculum -- Section V. The Schools and the employment of youth: success and opportunity -- Section VI. Federal aid to educations: considerations, complexities, and commitments -- Section VII. Some directions and possible remedies.
Includes index.
Keywords: COMMUNITY AND SCHOOL